On synchronization of symmetrically perturbed systems with quadratic nonlinearity - Dobrynskii, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish several synchronization conditions for the dynamics of symmetrically perturbed systems with quadratic nonlinearity.